Fecal carriage of extended-spectrum β-lactamase- and AmpC- producing Escherichia coli among healthcare workers - Rasha H. Bassyouni; Sylvana Nady Gaber; Ahmed Ashraf Wegdan (Journal of Infection in Developing Countries)
Introduction: Commensal E. coli can be considered a reservoir of genes coding for antibiotic resistance that may be transmitted in hospitals by healthcare workers (HCWs). This study aimed to determine the fecal carriage rate of extended-spectrum β-lactamase (ESBL)-producing E. coli among HCWs. Methodology: Stool samples were collected from 200 HCWs. Phenotypic screening for ESBL and AmpC β-lactamases was performed using disk diffusion and minimum inhibitory concentration methods followed by the combined disks test and double synergy differential test for confirmation. Multiplex polymerase chain reaction (PCR) was used to detect blaSHV, blaTEM, blaCTX-M, and CIT groups for AmpC genes. Results: Of 200 E. coli isolates, 100% were susceptible to imipenem, and 59 (29.5%) were resistant to one or more third-generation cephalosporins. By molecular analysis, 21% (42/200) were colonized by ESBL-producing E. coli, and 3% (6/200) were colonized by AmpC-producing E. coli. The blaSHV gene was the predominant ESBL gene, detected in 81.8% of the resistant E. coli isolates. Conclusions: These findings highlight the increase in fecal carriage of E. coli carrying ESBL and AmpC genes among HCWs, which may be one of the causes of the spread of ESBL-producing bacteria in hospitals and requires sound infection control measures. This is the first study of the fecal carriage rate of E. coli carrying AmpC genes in HCWs.